Effect of short-term naturopathy and yoga intervention on anthropometric variables, lipid profile and thyroid profile in obese hypothyroid patients: a randomised controlled trial - Shetty, Geetha B.; Shetty, Balakrishna; Shetty, Prashanth (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Hypothyroidism reflects decreased thyroid function and is one of the most common conditions seen in clinical practice. Practice of naturopathy and yoga has shown improvement in anthropometric variables and lipid profile in obesity and other chronic diseases. So, the aim of this study was to find out the effect of naturopathy and yoga in obese hypothyroid patients. Methods: A total of 60 subjects, of which 29 males (age 44.2±7.0 years) and 31 females (age 40.6±7.4 years) with body mass index (BMI), ≥30 were randomly assigned to case group (n=30) and wait list control group (n=30). The subjects of case group underwent naturopathy and yoga intervention for 10 days. Anthropometric variables, viz., body weight, BMI, waist circumference (WC) and hip circumference, serum lipid profile, and serum thyroid profile were assessed at 1st day (pre), at the end of 10 day (post). Results: The result showed a significant reduction in body weight, BMI, WC, total cholesterol, low density lipoprotein-cholesterol (LDL-C) and thyroid stimulating hormone (TSH) along with significant improvement in high density lipoprotein-cholesterol (HDL-C) in case group compared with control group in independent samples t test. Significant reduction in body weight, BMI, total cholesterol, LDL-C and TSH were observed in case group unlike in control group in student’s paired t test. Conclusions: Reduction in the body weight, BMI and improvement in serum lipid profile and serum thyroid profile in case group subjects compared to control group suggest that naturopathy and yoga have therapeutic and protective effects in the management of obese hypothyroid patients.